Analisis Tingkat Kerawanan Gerakan Tanah Desa Tontayuo, Kecamatan Batudaa Pantai, Kabupaten Gorontalo - Ana Saputri R Yahya; Ahmad Zainuri; Noviar Akase (Universitas Negeri Gorontalo, 2026)
Tontayuo Village, Batudaa Pantai District, Gorontalo Regency is an area with hilly topography and morphological characteristics with variations in slope gradients as well as lithology and rainfall conditions that have the potential to trigger landslides. This study aims to analyze the lithology of study area and the level of landslide vulnerability in the area. The research methods include field geogogical mapping, secondary data processing, and spatial analysis based on Geographic Information System (GIS). Assessment of landslide vulnerability levels is based on slope gradient parameters, lithology types, rainfall, lineament density, and land cover. The results of the study show that the lithology that makes up the study area includes basalt, granodiorite, limestone, and alluvial units. Based ono the analysis results, the level of landslide vulnerability in the study area can be categorized into 3 (three) classes, namely, low landslide vulnerability class (29,93 ha), medium landslide vulnerability class (178,3 ha), and high landslide vulnerability class (197,38 ha).